2015
DOI: 10.3989/scimar.04143.16a
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the age of sardine juveniles (<em>Sardina pilchardus</em>) from otolith and fish morphometric characteristics

Abstract: Summary: An age prediction model based on individual morphometric characteristics (total length; weight) and otolith morphometric characteristics (diameter; weight) was investigated for juvenile sardine, Sardina pilchardus (Walbaum, 1792). Juveniles were collected from northern Portugal between May 2004 and January 2005. Daily growth rings were counted on the otoliths of 114 juveniles of 7-16 cm total length. The sample was divided into a training sample used to develop the age prediction model and a test samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The birth date determined in December 2013 in the present study is consistent with observations for S. pilchardus in the wild. Our estimates of age-length relationship based on this birth date determination are in the range of the age-length relationship previously proposed by Silva et al (2015) for the same species.…”
Section: Ageingsupporting
confidence: 76%
See 1 more Smart Citation
“…The birth date determined in December 2013 in the present study is consistent with observations for S. pilchardus in the wild. Our estimates of age-length relationship based on this birth date determination are in the range of the age-length relationship previously proposed by Silva et al (2015) for the same species.…”
Section: Ageingsupporting
confidence: 76%
“…It was, however, well under what was previously estimated using Von Bertalanffy growth model in the Alboran sea (Alemany et al, 2006) and in the Gulf of Lions (Van Beveren et al, 2014), with 24 cm and from 18.38 cm to 33.57 cm, respectively. Using a Gompertz growth model, Silva et al (2015) estimated an even lower theoretical maximum length (14.3 cm) than us for sardines from the northwest coast of Portugal. The narrow range of observations in total length or weight in the present study certainly prevented from getting realistic estimates of the asymptotic weight and total length although the temperature forcing was included in the model.…”
Section: Bioenergeticsmentioning
confidence: 51%
“…In the same way, Silva et al (2015) made the prediction of the age of juveniles of sardine, Sardina pilchardus (Walbaum, 1792), from otolith and fi sh morphometric characteristics. The authors revealed that morphometric variables examined, otolith weight, diameter, fi sh total length and weight, were linearly related to the logarithm of age in sardine juveniles being 109-280 days old.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, age determination is difficult for most species, especially on living animals. Some methods involve using age-specific characteristics like tooth eruption and dental wear [1,2] , skeletal morphology [1,3] , body morphometrics [4] and bone ossification [5] , although most of these are applicable only after death. In addition, radiocarbon dating and aspartic acid racemization can serve as a tool for age estimation [6,7] , but again, not for living animals.…”
Section: Introductionmentioning
confidence: 99%